External-focus feedback benefits free-throw learning in children - Perreault, M. E.; French, K. E. (Research Quarterly for Exercise and Sport, 2015)
Purpose: Considerable research supports the motor-learning advantage associated with an external focus of attention; however, very few studies have attempted to generalize these findings to children especially with attentional focus feedback. Therefore, the purpose of this study was to determine the effect of attentional focus feedback on motor learning in children. Method: Boys (n = 14) and girls (n = 14) aged 9 to 11 years old were randomly assigned to 1 of 2 gender-stratified groups: (a) internal-focus feedback or (b) external-focus feedback. Following initial instructions and task demonstration, participants performed 100 modified free throws over 2 days while receiving feedback statements respective to their attentional focus condition. Approximately 24 hr later, participants performed a retention test consisting of 20 additional free throws. Participants were also asked to respond to a retrospective verbal report at the end of each day to serve as a manipulation check. Results: Results of the analysis revealed a statistically significant learning advantage for participants receiving external-focus feedback, and retrospective verbal reports provide support for the self-invoking trigger and constrained action hypotheses. Conclusions: Future research should continue to incorporate retrospective verbal reports and explore potential causal links between internal attentional focus and self-evaluation.